The Effectiveness Of WFH Work System Implementation On Employee Performance In Dinas Pendidikan, Medan City - Imsar Imsar; Nurhayati Tariani; Yoesrizal M. Yoesoef (Journal of Management and Business Innovations, 2020)
This paper aims at the effectiveness of the application of the WFh (Work Form Home) work system on the performance of employees at the Medan City Office. In the Medan city education office itself, it has implemented a Work Form Home (WFH) work system that has been running for one year, where only part of the employees who work at the location continue to apply health protocols by always using masks and maintaining distance in carrying out their duties. Meanwhile, some other employees carry out official duties in their respective homes, this is done alternately from day to day. In implementing the Work Form Home (WFH) work system, of course, it has an impact on employee performance problems because it cannot be directly supervised by the institution. Performance problems are seen from various aspects such as the ability of ASN employees to complete their work even though they have to work at home and the improvement in the results that should be obtained for work by employees. Work quality, work motivation and work morale that affect the performance of ASN employees, especially in the Medan City Education Office. The results showed that the WFH (Work Form Home) system implemented at the Medan City Office was less effective in improving employee performance.Keywords: Department of education, effectiveness, performance, work from home (WFH)